(untitled) (Al-Academy, 2019)
Advertising design is one of the arts of communication of various levels and one of the aspects of the fields of design arts, and that the construction of the design environment in the advertising is one of the important entry points in making the recipient feel this environment and feel as if being one of its elements. It is an entrance worthy of study and research and is a problem worth raising according to the following question: - What is the effectiveness achieved in the virtual design environment for digital advertising? The two researchers dealt with the research in three frameworks, the methodological framework which identified (the problem of research, its importance, purpose, limits, and the definition of terms) and then the theoretical framework with two sections , the first is the virtual design environment, and the second is digital processing of the virtual design environment, and then the procedural framework down to the most important results: The virtual perceptions achieved clarification and a statement of the characteristics and contents of advertising through the advertising idea and its communication goal resulting from the objective construction of the design environment, as the virtual perception of the advertising concept multiplied in varying proportions. The objective embodiment function of the design environment was achieved through the advertising image in symbolic expression